Expanding the Domain of Festival Research: A Review and Research Agenda. (15th February 2016) - Wilson, Juliette; Arshed, Norin; Shaw, Eleanor; Pret, Tobias
Abstract : Festivals are an important sub‐field within event studies which, until recently, have not been studied as separate experiences. A systematic review of the emerging literature on festivals reveals several key characteristics. While festivals are diverse in nature and geographical location, scholarly interest focuses on five main themes: the motivations for organizing, funding and attending festivals; the experiences of festival attendees; the relationship between festivals and their local environments; the economic and sociocultural impacts of festivals; and the management of festivals. Despite growing interest in festivals as research sites, little attention has been afforded to investigating festival processes. In particular, considerations of how festivals are established, and which individuals are involved in their initiation and regular staging, offer opportunities for research. This paper highlights the significant role festivals play within their local communities, including their facilitation of social cohesion and regional identity. Our study reveals that the literature rarely discusses the development of festivals over time and the wider networks in which festivals are embedded. This critical review of festival research identifies various research gaps and directions for future research to develop theory and practical understanding of festivals.